Determinant Factors of Father Involvement in Early Childhood with Disabilities: A Systematic Review - Ajeng Hayyu Sujalmo; Achmad Chusairi (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
Fathers are the primary provider of support for the family and are crucial to the child's successful development, therefore it is crucial that they are involved. This research aims to explore factors of father involvement in young children with disabilities. Articles in this research were searched through the ScienceDirect, Scopus, Proquest and Web of Science databases. After that it was reviewed using the PRISMA-ScR procedure. This research used six journal articles which were included based on exclusion and inclusion criteria and used the metasynthesis method. The results of comprehensive findings of father involvement factors: mother factors, father factors, contextual variables, parent-child relationships and child factors. The conclusion is that the relationship between father involvement and caring for early childhood children with disabilities are two things that cannot be ignored. Future research could use the context of father involvement as a diverse construct.